2006
DOI: 10.1177/000313480607200812
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transgastric Removal of an Eroded Angelchik Prosthesis

Abstract: The Angelchik prosthesis is a silicone gel-filled implant historically placed around the gastroesophageal junction for the treatment of gastroesophageal reflux disease. Herein, we describe the laparoscopic transgastric removal of an Angelchik prosthesis that had eroded through the gastroesophageal junction of a patient 25 years after its placement. Under direct laparoscopic and endoscopic guidance, laparoscopic trocars were placed transabdominally, directly into the gastric lumen. Using 2-mm instrumentation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Due to its high complication rate, many patients underwent removal of the AD 2 7 12 13. Recent literature has reported successful removal of AD laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high complication rate, many patients underwent removal of the AD 2 7 12 13. Recent literature has reported successful removal of AD laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…Underwood et al 13 described the resolution of dysphagia in a patient who continued to have only mild reflux symptoms following laparoscopic removal of AD. Another case reported by Carbonell and Maher12 described the removal of the AD via a laparoscopic, transgastric approach to retrieve an AD that had eroded through the gastrointestinal junction. Jalil et al 14 described the laparoscopic removal of Angelchik prosthesis followed by an immediate Nissen’s fundoplication in a patient who had an AD for over 20 years 14.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Carbonell et al reported a case of prosthesis erosion into the GEJ, necessitating transgastric removal 25 years after placement, an approach chosen to avoid entry of the fibrous capsule surrounding the device. 11 Authors have described endoscopic removal of eroded prostheses, which allows patients to avoid potentially morbid surgical procedures. 9 Recurrent GERD symptoms can occur as late as 15 years after prosthesis placement.…”
Section: Discussionmentioning
confidence: 99%
“…In the stepwise experience, the advantages of laparoscopy appeared to be enhanced by the hybrid NOTES approach: patients had minor postoperative pain and minimal scarring, and recovered soon 25–31 …”
Section: Discussionmentioning
confidence: 99%